THE IMPORTANCE OF CHILD REHABILITATION AFTER COCHLEAR IMPLANTATION - Rakhimova Khurshidakhan Sadikovna; Teshaboyeva Muhlisahan Nodirbek Daughter (Galaxy International Interdisciplinary Research Journal, 2023)
The article will focus on creating the necessary conditions for the successful development of speech of children with hearing impairment after cochlear implantation, fine-tuning the children’s general speech processor, developing language - communication skills, developing oral speech, as well as providing guidance to the child and his family on the use of the apparatus, providing them with psychological assistance.